Curriculum studies scholarship in the context of contemporary world crises - Simmonds, Shan; Maistry, Suriamurthee (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
Refer to the document
Journal article published in the African Perspectives of Research in Teaching and Learning Journal Issue 5, Volume 9, 2025 Special Issue
Keywords: Curriculum studies scholarship; Geopolitical conflicts; Interdisciplinary approach in education; Education -- Curricula; Curriculum planning; Geopolitics